Since the common difference is 6, we can assume that the sequence is arithmetic, with rule
T(n)=6n+5 where T(1)=11
T(9)=6(9)+5=59
Answer:
Step-by-step explanation:
6⁻︎¹(4⁻︎²)
1/6x1/4 2
1/6 x 1/16
1/96
2x-1.1/4+x/3=2
2x-1/4+x/3=2
2x-1/4+x/3+1/4=2+1/4
2x+x/3=9/4
3(2x+x/3)=3.94
7x=27/4
7x/7=27/4/7
x=27/8
<h2>PLEASE MARK ME AS BRAINLIEST IF U LIKE MY ANSWER AND SORRY FOR GIVING THE ANSWER LATE BECAUSE I'VE GIVEN U ANSWER FROM MY LAPTOP PLEASE TELL THAT IT'S CORRECT OR NOT</h2>
Anserr what the question?
Step-by-step explanation: